Theoretical Insights into the Mechanism of CO2 Chemisorption and Subsequent CO Desorption on Char Surface with Zigzag Active Sites. Issue 7 (2nd July 2016) - Liu, Peng; Lin, He; Huang, Zhen
ABSTRACT: A detailed mechanism accounting for CO2 chemisorption and subsequently CO desorption on char surface with zigzag active sites has been investigated using accurate ab initio density functional theory B3LYP/6-311+G(d, p) calculations. The HOMO-LUMO gaps indicate that char donates electrons to CO2, which is tempted by small electron confinement capability of the surface active C atom. In single-site adsorption, the carbonyl-type oxygen groups can be formed, whereas the heterocyclic oxygen and the lactone groups can be formed via dual-site adsorption. It was found that the former process is endothermic and the latter process is exothermic. In this study, CO2 chemisorption products can be influenced by the electronic environment in terms of the optimized bond length. The reaction channels accounted for CO desorption from char-CO2 complex and the evolution from lactone group to a cyclic ether structure were determined. The rate coefficients were evaluated by transition state theory theory in the temperature range of 300–2500 K. The results showed that the CO desorption reaction is competitive, and the evolution from lactone group to a cyclic ether structure is kinetically supported. In addition, the carbonyl-type oxygen groups are more likely converted from heterocyclic oxygen groups instead of direct single-site adsorption.